Teachers’ Implementations of Teaching Techniques for Young Learners - Veronica Listyani Diptoadi; Ruruh Mindari; Hendra Tedjasuksmana (Celt: A Journal of Culture, English Language Teaching & Literature, 2018)
Although often taking part in seminars and workshops on how to teach English to their students, it seems that elementary school teachers of English (though not all) do not really implement what they have received in their classrooms. The seminar that the English Department of Widya Mandala Surabaya Catholic University held on the 8th of August 2015 was a workshop where the participants, the elementary school teachers of English, were trained to demonstrate how to use drama, storytelling, games and songs as techniques in teaching English to their students. They were expected to be able to use these techniques in their respective classrooms. The techniques became the alternatives to the current techniques being practiced at schools to enliven the learning atmosphere. Therefore, this study which is the third level or the last level of our project on developing an English handbook for English teachers at elementary schools, is in the form of an observational study describing how the teachers implemented the techniques -- drama, storytelling, games and songs -- in their respective classrooms, students’ responses and   what problems took place when the teachers were carrying out the techniques. The results show that the teachers were able to teach those techniques in their classes, students actively took part more actively in their English class, and they liked games and songs much.